Kajian Efisiensi Bank Umum Syariah di Indonesia - Siti Karimah; Tanti Novianti; Jaenal Effendi (AL-MUZARA'AH, 2016)
The aim of this study is to measure the efficiency of Islamic Bank in Indonesia and to analyze the factors that affect the level of efficiency. The objects of this study are ten Islamic Bank (BUS) in Indonesia which analyzes from the second quarter of 2012 until the first quarter of 2016. There are three method which are used in this study, two in first stage, namely non parametric method of Data Envelopment Analysis (DEA) and parametric method of Stochastic Frontier Approach (SFA) then the second stage is Tobit estimaton. Overall, the results showed that the efficiency level of Islamic banks in Indonesia during the time period in this study have not reached the optimum level of efficiency yet. Tobit estimation showed that total financing, total wadiah funds, CAR, ROE, total overhead cost significantly affect the Islamic bank`s efficiency in Indonesia.